Abordagem familiar: uma teoria sobre a experiência de enfermeiros na estratégia saúde da família - Evandro de Souza Queiroz (2015)
The family has always been the basis for health care, even when public policies did not make that recommendation. In Brazil, the first political appointments for the family started up from the creation of the Public Health System and the Family Health Strategy. Currently, despite the initial breakthrough provided by this strategy, what we see is the distance of the original guidelines in relation to family care. Thus, the objective of this research was to build theory about the family approach carried out by the nurse in the Family Health Strategy. It is a qualitative study, with theoretical framework in Symbolic Interaction and methodological framework on Grounded Theory. They interviewed 26 nurses working in the Family Health Strategy. The result was the creation of the Family Theory Approach for nurse in the Family Health Strategy, with four main categories. The first, called Family Conceptions, presents the concept of family originated from the nurses experiences. The second, named Social Conjuncture, defines the context where the family concepts are determined and the family approach occurs. The third, called Health Conjuncture, presents the situational elements in health that have influence on the family approach. And the last, the very Family Approach, presents the elements that involve the care provided by nurses in this scenario. The main contributions of this study are intended for Nursing and the Family Health Strategy, through the systematic theory about the family approach. This study also presents considerations about the use of familiar approach tools, the training of nurses for the work in the family health strategy and policy documents for family health in Brazil.